Effect of tillage practices on soil moisture status and performance of Pearl millet cultivars under rainfed conditions - PAREEK, N. K.; VERMA, JITENDRA KUMAR; GODARA, S. L.; KUMAR, ANAND (Journal of Soil and Water Conservation, 2018)
A field experiment was conducted at Research Farm, SKRAU, Bikaner for two consecutive years during kharif 2014 and 2015 to determine the effect of tillage practices on yield, economics and soil moisture status of pearl millet [Pennisetum glaucum (L.) R.Br.] cultivars under rainfed situations. Treatments comprised of four tillage practices in main plots (conventional tillage, zero tillage, conventional tillage + ridging and zero tillage + ridging) and four cultivars of pearl millet in sub plots (Pusa composite 443, CZP 9802, MPMH 17 and RHB 177) were laid out in split plot design with four replications. Pooled analysis of result indicated that practice of conventional tillage + ridging and zero tillage + ridging significantly increased the grain and straw yields and the grain yield increased to the tune of 10.25 and 8.53 per cent, respectively, over conventional tillage. The treatment zero tillage + ridging recorded the highest net return (Rs. 19,250 ha-1) and B: C ratio (3.03) among all the tillage practices and resulted in Rs. 3750 ha-1 higher net return in comparison to conventional tillage. Significantly higher values of field water use efficiency (FWUE) and soil moisture content (SMC) were also observed under zero tillage + ridging than conventional tillage. Pearl millet hybrids (MPMH 17 and RHB 177) were recorded significantly higher grain yield, harvest index, FWUE and SMC in comparison to composite cultivars. The hybrid MPMH-17 was recorded the highest grain yield (1176 kg ha 1), harvest index (30.18%), net return (Rs. 19,413 ha-1) and B: C ratio (2.86) and was at par with that of cv. RHB 177. Hybrid MPMH 17 gave the highest net return of Rs. 21682 under conventional tillage + ridging treatment and remained at par where cv. MPMH 17 or RHB 177 when grown under zero tillage + ridging.